Effects of concurrent training associated with N-acetylcysteine on bone density of spontaneously hypertensive rats - Murillo Martins Rogerio; Lucas Silva Santos; Thiago Alves Garcia; Guilherme Akio Tamura Ozaki; Rodrigo Antonio Fernandes; Robson Chacon Castoldi; Mario Jefferson Quirino Louzada; Katashi Okoshi; Adriana Junqueira
Abstract Aim: The present study aimed to analyze the effects of N-acetylcysteine supplementation associated with concurrent training on the bone mineral density of spontaneously hypertensive elderly rats. Methods: For the present study, 28 male spontaneously hypertensive rats, six months old, were distributed in the following groups: control (C, n=7); control + N-acetylcysteine (CNAC, n=7); concurrent training (T, n=7); and concurrent training+N-acetylcysteine (TNAC, n=7). The concurrent training was composed of aerobic training on a treadmill and resistance training in the same training session, three times a week. Animals of the NAC groups received a dose equivalent to 120 mg/kg/day orally for eight weeks. The animals in the trained groups underwent training for eight weeks. The animals were evaluated at the beginning and end of the experiment. After euthanasia, the tibias and femurs were submitted to bone densitometry analysis in an X-ray dual emission device. Results: Lower weight variation was observed in the trained animals and a reduction in pressure values in all groups, but without a statistical difference (p> 0.05). The animals in the T and TNAC groups presented a better performance in the physical tests (p <0.05). In relation to bone, the NAC groups demonstrated a decrease in femoral bone density when compared to groups C and T. Finally, all experimental groups demonstrated an increase in tibial bone density, but with no statistical difference (p>0.05). Conclusion: The animals in group T demonstrated better performance in the physical tests. In addition, the NAC caused a reduction in the bone mineral density of the femur.